THE EFFECT OF THE SOCIAL MEDIA INSTAGRAM @UNTIDAR.OFFICIAL FULFILLMENT THE INFORMATION NEEDS OF FOLLOWERS - Aldilla Kurnia Eka Savita; R. Yogie Prawira; Hindina Maulida (Acta Diurna: Jurnal Ilmu Komunikasi, 2026)
Instagram is one of the social media platforms widely used as a means of disseminating information, including by educational institutions. Therefore, this study was conducted with the aim of determining and explaining the effect of using the Instagram social media account @untidar.official on meeting the information needs of followers using the Uses and Gratifications Theory. This study used a quantitative method. Data analysis techniques used validity tests, reliability tests, classical assumption tests, and simple linear regression analysis. The results of the study indicate that the use of Instagram @untidar.official social media has a significant effect on meeting the information needs of followers.